Hormonal Control of Important Agronomic Traits - Chi-Kuang Wen (Frontiers Research Topics, 2018)
One of the goals of plant science is to improve agricultural sustainability, increasing yield, food diversity, and nutrition, while minimizing the negative impact on our environment. In response to internal and external cues, plant hormones control various aspects of plant growth and development. The wealth of our knowledge on plant hormones shall greatly advance sustainable agriculture.